Arkeologi Pemukiman: Titik Strategis dan Beberapa Paradigma - Heddy Shri Ahimsa-Putra (Balai Arkeologi Yogyakarta, 1995)
The relationship between humans and space is one of the many human relations studied by anthropologists. In relation to archaeological studies, the form of this relationship is evident in human settlements and the patterns they produce, whether consciously or not. Settlement patterns are an embodiment (expression) of the human conception of space, and are the result of human efforts to change and utilize their physical environment based on their views and knowledge about the environment.